Centre of engineering pedagogy in Kazan - V. . Ivanov; L. . Gurie (Высшее образование в России)
The article considers preconditions and factors of formation of engineering pedagogy as a branch of pedagogical knowledge, traces its development within the research school of the Kazan national research university.